PENGARUH GREEN HRM TERHADAP PERILAKU KARYAWAN YANG DI MEDIASI GREEN RECRUITMENT, GREEN TRAINING DAN GREEN WORK ENGAGEMENT - Rizqi Muhammad Sholeh; Jati Waskito (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the influence of Green Hrm on Employee Behavior mediated by Green Recruitment, Green Training and Green Work Engagement. This type of research uses a quantitative method. The population in the study is employees who work in coffee shops in the Soloraya area and its surroundings. The number of samples in this study is 40 employees of coffee shops operating in the surrounding Soloraya. The data source used in this study uses primary data. The data collection method uses a questionnaire method. The sampling technique in this study uses Purposive sampling. The data analysis in this study was carried out using the Partial Least Square (PLS) method using SmartPLS software version 3.02. The results of this study are that Green human resources management and Green Recruitment do not have a significant influence on employee behavior. Green Recruitment does not mediate the relationship between Green human resources management and employee behavior. Green Training has a positive and significant influence on employee behavior. Green Training mediates the relationship between Green human resources management and employee behavior. Green work engagement does not have a positive and significant influence on employee behavior. Green work engagement does not mediate the relationship between Green human resources management and employee behavior